The cycling boom in large German cities. Empirial evidence for successful cycling campaigns. - Lanzendorf, Martin; Busch-Geertsema, Annika (Elsevier, 2014)
Historically, the promotion of cycling has been neglected in most German cities with more than 500,000 inhabitants. In the last 15 years, however, some cities discovered the advantages of increasing the cycling share for both life quality and a more sustainable transport system in their cities. This paper focuses on four case studies from the German cities of Munich, Hamburg, Berlin and Frankfurt, and investigates both the development of cycling policies and the changing use of the bicycle as mode of daily transport between 2002 and 2008 in these cities. By analysing policy documents, web sources and national travel data, we show (1) that the often claimed increase of cycling usage in Munich, Frankfurt and Berlin is supported, and (2) identify the implementation and strengthening of policies to promote cycling by the local government as crucial for these successes. These findings are supported by our fourth case study, Hamburg, where we were not able to identify an increased bicycle usage in this time period, where cycling promoting policies were adapted by the local government only in 2008 and, thus, effects can only be expected after 2008. Our findings support that, although local cycling policies are not the only factor for successfully increasing cycling usage, they play a crucial role in the process of increasing cycling use in cities. Both, cycling infrastructure improvements and communication campaigns, initiated, supported and executed by the local government, are key factors for increasing bicycle use in cities.
Keywords: Fahrrad; Verkehrspolitik; Kommunikation; Fahrradförderung; Radverkehrsförderung; Fahrradinfrastruktur; Radverkehrsplan; Radverkehrskampagne; Kampagne; Nachhaltige Mobilität